Oligosarcus perdido (Characiformes, Characidae), a new species of freshwater fish from Serra da Bodoquena, upper Rio Paraguai basin, Brazil - Ribeiro, Alexandre C. [UNESP]; Cavallaro, Marcel R.; Froehlich, Otávio (My University, 2007)
Oligosarcus perdido, a new species of freshwater fish from Serra da Bodoquena, upper Rio Paraguai basin, Brazil, is described. The new species is distinguished from congeners by the number of lateral-line scales, number of scales around the caudal peduncle, and osteological characters. The osteology of this new species is also documented by stereomicroscopic photography of cleared and stained specimens. Ecological notes based on direct observation by scuba diving in the field are also provided. Copyright © 2007 Magnolia Press.
Keywords: Freshwater fishes; Neotropical region; Taxonomy; Characidae; Characiformes; Oligosarcus; Pisces